Perlindungan Hukum Bagi Justice Collaborator Dalam Pengungkapan Tindak Pidana Pembunuhan Berencana - Aprillia Krisdayanti (Universitas Islam Indonesia, 2022)
The focus of this research is the legal protection of justice collaborators for criminal act of murder in Indonesia in regards to the premeditated murder cases. The main objective is to identify the obstacles faced in providing legal protection for witnesses and victims of murder. The type of the research is normative juridical with statutory and conceptual approaches. The research results concluded that: First, the existence of a justice collaborator is crucial and hence sits under the spotlight in determining the existance of the case, the original timeline of the murder, what tools used by the killer, where the murder took place, to the point where the perpetrators involved in the murder were exposed so that the crime could be completed. Second, the obstacles found in the implementation of legal protection for justice collaborators are those contained in the provisions of the law, the institutional constraints, and the constraints on inter-agency cooperation.Keywords: Justice Collaborator, Legal Protection, Premeditated Murder Crime AbstrakFokus penelitian ini adalah perlindungan hukum justice collaborator tindak pidana pembunuhan di indonesia terkait kasus pembunuhan berencana. Adapun tujuan utamanya adalah untuk mengetahui kendala apa yang dihadapi dalam memberikan perlindungan hukum bagi saksi dan korban tindak pidana pembunuhan. Tipe penelitiannya adalah yuridis normatif dengan pendekatan perundang-undangan dan pendekatan konseptual. Hasil penelitian menyimpulkan; Pertama, keberadaan seorang justice collaborator sangat penting bahkan menjadi titik terang dari kasus yang ada, garis waktu asli pembunuhan itu, alat apa yang digunakan sang pembunuh, dimana pembunuhan itu terjadi, hingga para pelaku yang terlibat dalam pembunuhan tersebut diungkap agar kejahatan tersebut dapat selesai. Kedua, Kendala yang didapatkan pada suatu pelaksanaan perlindungan hukum justice collaborator yaitu terdapat pada aturan dalam Undang-Undang, kendala kelembagaan, dan kendala kerjasama antar lembaga.Kata-kata Kunci: Justice Collaborator, Perlindungan Hukum, Tindak Pidana Pembunuhan Berencana